Clinical case studies in home health care - Neal-Boylan, Leslie (Hoboken, New Jersey : Wiley-Blackwell a John Wiley & Sons, Inc., Publication, 2011)
Home health care is an important aspect of community health and a growing area of healthcare services. Clinical Case Studies in Home Health Care uses a case-based approach to provide home healthcare professionals, educators, and students with a useful tool for thoughtful, holistic care. The book begins with a thorough and accessible introduction to the principles of home health care, including a discussion of supporting theoretical frameworks and information on managing complexities, transitioning patients to home care, and preparation for the home visit. Subsequent sections are comprised entirely of case studies organized by body system. Though cases are diverse in content, each is presented in a consistent manner, incorporating relevant data about the patient and caregivers and the approach to patient care and promoting a logical approach to patient presentation. Cases also include helpful tips about reimbursement practices, cultural competence, community resources, and rehabilitation needs.
Clinical Case Studiesin Home Health Care; Table of Contents; Contributors; Preface; Acknowledgments; Section 1: Introduction; Theoretical Frameworks That Support Home Care; Managing the Complexities of Home Health Care; Transitioning; The Home Visit; Section 2: Cardiac; Case 2.1 Congestive heart failure; Case 2.2 Atrial fibrillation; Case 2.3 Wound following a coronary artery bypass graft (cabg); Section 3: Peripheral Vascular Disease; Case 3.1 Peripheral vascular disease; Section 4: Pulmonary; Case 4.1 Chronic Obstructive Pulmonary Disease (COPD); Case 4.2 Pneumonia; Case 4.3 Tuberculosis. Section 5: GastrointestinalCase 5.1 Stomach Cancer; Case 5.2 Malnutrition/Anemia; Section 6: Genitourinary; Case 6.1 Neurogenic bladder; Case 6.2 Urostomy Care; Case 6.3 Urinary Tract Infection and Functional Incontinence; Section 7: Psychiatric/Mental Health; Case 7.1 Bipolar Disorder; Case 7.2 Personality Disorders; Case 7.3 Schizophrenia; Case 7.4 Schizoaffective Disorder; Section 8: Musculoskeletal; Case 8.1 Muscular dystrophy; Case 8.2 Cerebral Palsy; Case 8.3 Osteomyelitis, decubitus ulcer, and paraplegia; Section 9: Neurological; Case 9.1 Brain stem infarct. Case 9.2 Multiple SclerosisSection 10: Maternal Health; Case 10.1 Antepartum care; Case 10.2 Postpartum care following uncomplicated delivery; Case 10.3 Postpartum care following complicated delivery; Section 11: Pediatrics; Case 11.1 Premature infant with apnea and refl ux; Case 11.2 Asthma; Case 11.3 Adolescent with neurodevelopmental disability; Section 12: Pediatric Intensive Care; Case 12.1 Alpha thalassemia X- linked mental retardation syndrome; Case 12.2 Anoxic brain damage/achondroplasia; Case 12.3 Cerebral palsy/ acute respiratory failure; Section 13: Infectious Disease. Case 13.1 Clostridium difficile-Associated disease (CDAD)Case 13.2 Community-Associated, methicillin-Resistant Staphylococcus aureus (MRSA); Case 13.3 Influenza; Section 14: Endocrine; Case 14.1 Diabetes Mellitus Type 1; Case 14.2 Diabetes Mellitus Type 2; Section 15: End-of-Life Care; Case 15.1 Grief; Case 15.2 Palliative care; Case 15.3 Hospice; Case 15.4 Amyotrophic lateral sclerosis; Index.
Includes bibliographical references and index.
Keywords: HOME CARE SERVICES -- CASE STUDIES